Photonic Crystals - Bananej, Alireza (IntechOpen, 2015)
As a reason of information explosion, electronic communication networks are not sufficient for high bit rate data transmission. This problem has been solved by optical networks which caused the birth of a new area of technology, photonics. In photonic circuits photons play the dominant role and they transfer the optical data. With the growth of the photonics technology, a new area started to grow as photonic crystals which now play an important role in designing and manufacturing compact photonic devices. Photonic crystals are structures with alternative dielectric constant in one, two or three dimensions which are called one, two or three dimensional photonic crystals. By using the properties of photonic band gap, many interesting phenomena such as slow light generation, dispersion engineering in a compact and low size device can be achieved.